Pengembangan Sistem Monitoring Server Hosting cPanel Berbasis Web Menggunakan Script Monitoring Pada PT. Tujuh Ion Indonesia - Purwanto Purwanto; Sufajar Butsianto; Edora Edora (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
PT. Tujuh Ion Indonesia, a technology company that specializes in hosting and domain services, heavily relies on server performance for their hosting solutions. To maintain server stability, both hardware and software monitoring are crucial. This research aims to develop a web-based server hosting monitoring system using scripting. The system allows monitoring critical server aspects, such as CPU, RAM, hard disk usage, and essential supporting applications in real-time. Data is displayed through an intuitive web interface. The study demonstrates the system's effectiveness in real-time server monitoring. Users can track server performance, obtain accurate information, and swiftly identify issues. Additionally, the system supports notifications through email and Telegram for threshold breaches or problems. In conclusion, this web-based server hosting monitoring system with scripting provides an effective solution for PT. Tujuh Ion Indonesia to maintain server performance stability. It enhances server monitoring efficiency and facilitates responsive actions to emerging issues.